2000
DOI: 10.1080/01904160009382009
|View full text |Cite
|
Sign up to set email alerts
|

Increased plant nitrogen loss with increasing nitrogen applied in winter wheat observed with15nitrogen

Abstract: Nitrogen (N) fertilizer is generally the most costly input for winter wheat (Triticum aestivum L.) production. Therefore, it was important to maximize fertilizer use efficiency and minimize N losses to the environment. One of the mechanisms responsible for decreased N use efficiency (NUE) was plant N loss. The objectives of this experiment were to determine fertilizer N recovery in winter wheat when produced for forage and grain, and to quantify potential plant N losses from flowering to maturity in winter whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
3
9
1
Order By: Relevance
“…However, the unaccounted N increased as applied N increased regardless of the source (Table 5). Lees et al (2000) observed similar trends in a study conducted to document unaccounted N using 15 N.…”
Section: Soil Nitrogen Phosphorus Potassium and Ph Statussupporting
confidence: 67%
“…However, the unaccounted N increased as applied N increased regardless of the source (Table 5). Lees et al (2000) observed similar trends in a study conducted to document unaccounted N using 15 N.…”
Section: Soil Nitrogen Phosphorus Potassium and Ph Statussupporting
confidence: 67%
“…In general, losses are expected to be higher when moisture stress occurs during this period. Nonetheless, climatic differences from one day to the next can alter these estimates even when using isotopic difference methods (Lees et al., 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Harper, Sharpe, Langdale, and Giddens (1987) found this aerial loss of 8.3 kg N ha -1 at 20-d post fertilizer application, and an additional 7.1 kg N ha -1 loss from anthesis to harvest. Lees, Raun, and Johnson (2000)) noted a 12 kg N ha -1 gain to 42 kg N ha -1 loss from flowering to maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the plant usually attains maximum nutrient uptake at the flowering to ripening stage (Karlen et al, 1987;Rodriguez et al, 1990), and Downloaded by [University of California Santa Cruz] at 06:33 27 November 2014 a decline in maximum nutrient uptake may decrease the potential for nutrient translocation from vegetative to reproductive organs. Secondly, many studies have reported that nutrient losses may happen later in the crop growing season, especially loss of N (Bashir et al, 1997;Lees et al, 2000). Therefore, the more nutrient that is lost the less there is to be translocated to filling seeds.…”
Section: Nutrientmentioning
confidence: 98%